The Role of Glutamine in Muscle Regeneration and Recovery: A Literature Review - Redner, Aneta; Głowacz, Julia; Popiel, Michał; Kulig, Klaudia; Wiśniowski, Maksymilian; Dziekoński, Kamil; Rybowski, Jakub; Zwierzchlewska, Patrycja; Buczek, Kacper; Gorycki, Hubert; et al. (Quality in Sport, 2025)
Purpose: The purpose of this review is to analise current scientific literature regarding the impact of glutamine supplementation on muscle repair, post-exercise recovery, and skeletal muscle preservation. It also examines the biological pathways through which glutamine may exert its effects, including modulation of inflammation and enhancement of protein turnover. Methodology: A review of scientific literature was performed, focusing on studies investigating the effects of glutamine supplementation on skeletal muscle recovery and function. The review includes experimental studies, clinical trials, and narrative reviews involving both athletic and clinical populations, with attention to various training conditions, health statuses, and supplementation strategies. Findings: The evidence indicates that glutamine can support recovery processes by mitigating muscle inflammation, improving redox balance, and promoting anabolic signalling. However, the degree of effectiveness varies, with more pronounced benefits observed in clinical and stress-related conditions compared to healthy individuals. The influence of dosage, supplementation timing, and individual variability remains a key consideration. Conclusions: Glutamine shows potential as a supportive agent in muscle regeneration, particularly in contexts of physical stress, illness, or injury. Further studies are needed to define its role in athletic, healthy populations and to optimize administration strategies based on individual needs and health status.